O nazewnictwie w nauce o ruchach ludzkich - Petrynski, W. (Human Movement, 2002)
The paper is focused on the problem of harmful influence of language incoherencies on the quality of scientific models. As an example there have been presented two schemes from the papers by R. Schmidt, along with proposals of improving the terminology, both in Polish and in English. There has been shown a close relation between the terminology and quality of a general model of human performance. The main thesis of the paper is that in science the words are not only passive means of communication, but also an active building material of scientific models. Hence, the quality of the description language strongly influences the quality of the model itself. As an example there is presented a scheme of Critical events involved in the reaction time paradigm taken from the handbook by R.A. Schmidt (Fig. 1). It suggests that there exists a difference between "reaction" and "response", but does not explain the difference. There is no definition of the terms in any of the books by Schmidt. Moreover, in common dictionaries both terms are synonyms. In this case it would be highly recommended to adopt the "Ockham's razor" and eliminate from terminology the excessive expression "reaction", which does not explain anything, but only produces an extra ambiguity. In the paper there have been presented corrected versions of the scheme. There are proposed names for particular parts of the motor response, in accordance with both their real sense and with common dictionary meanings. The adopted procedure is an example of refining the existing scientific model by using purely semantic analysis and carefully passing the model through the "filters" of two languages, English and Polish.Particular parts of the presented scheme could be ascribed to specific blocks in Schmidt's scheme of human movement performance. The next two terms, feedback and feedforward, are also analyzed. There are quoted four definitions of the term feedback, taken from four different books by Schmidt, which differ from each other, but none of them contains the very important element of the word "feed": its influence on the input into the system. Without such an influence one has to do with "back information" or "forward information"; only putting such information into the input of the system would justify calling them "feedback" or "feedforward". The feedforward mechanism has no reflection in Schmidt's scheme. In the paper there has been proposed a scheme version with the feedforward control mechanism, which imposes no great complication. It allows to include the elements of experience and anticipation into the scheme (Fig. 3). There is also discussed another inaccuracy, namely identification of terms "extrinsic feedback" and "augmented feedback", which by no means are synonyms and could not be adopted as equivalents. Linguistic carelessness seems to be especially a "mortal sin" in the case of famous scholars, because many scientists would uncritically follow them. This leads to misunderstanding of scientific models and produces "dead ends" in science. Hence, to ensure further normal development of human kinetics, it seems to be necessary to bring order into the terminology and to compile a multilingual, encyclopedic dictionary of our branch of science.